2010
DOI: 10.1158/0008-5472.can-09-4099
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Biomarkers for Predicting Nasopharyngeal Carcinoma Response to Radiotherapy by Proteomics

Abstract: Radiotherapy is the primary treatment for nasopharyngeal cancer (NPC), but radioresistance remains a serious obstacle to successful treatment in many cases. To identify the proteins involved in this resistance and to evaluate their potential for predicting NPC response to radiotherapy, we first established a radioresistant subclone cell line (CNE2-IR) derived from NPC cell line CNE2 by treating the cells with five rounds of sublethal ionizing radiation. Proteomics was then performed to compare the protein prof… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
177
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(180 citation statements)
references
References 36 publications
3
177
0
Order By: Relevance
“…A quantitative score was performed by adding the score of staining area and the score of staining intensity for each case to assess the protein expression levels as previously described. 47 At least 10 high-power fields were chosen randomly and 41000 cells were counted for each section. First, a quantitative score was performed by estimating the percentage of staining-positive cells: 0, no staining of cells in any microscopic field; 1+,o30% of cells stained positive; 2+, between 30 and 60% stained positive; and 3+, 460% stained positive.…”
Section: Methodsmentioning
confidence: 99%
“…A quantitative score was performed by adding the score of staining area and the score of staining intensity for each case to assess the protein expression levels as previously described. 47 At least 10 high-power fields were chosen randomly and 41000 cells were counted for each section. First, a quantitative score was performed by estimating the percentage of staining-positive cells: 0, no staining of cells in any microscopic field; 1+,o30% of cells stained positive; 2+, between 30 and 60% stained positive; and 3+, 460% stained positive.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have screened for DEPs associated with radioresistance in NPC (4,10). One study identified seven upregulated genes in radioresistant subclones of CNE2.…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to distinct tissue specificity or the different methods used. Although several radioresistant subclones of NPC have been established (3,4), no animal experiments have been reported thus far. As described previously (3), we have also established a subclone (CNE-2R) by exposing CNE-2 cells to a cumulative radiation dose of 64 Gy.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, NPC poses one of the most severe public health problems in these areas (1). The disease tends to be more sensitive to ionizing radiation (IR) than other head and neck cancers and, therefore, the primary treatment for patients with NPC is radiotherapy (2,3). Although the technology for radiotherapy has been improved, its therapeutic effects on NPC are unchanged.…”
Section: Introductionmentioning
confidence: 99%
“…The main reason for this is the existence of radioresistant cells in NPC tissues. These cells not only show resistance to radiation, but they also exhibit an increased invasive ability following radiotherapy (2,4,5). Some patients with NPC present with local recurrence and distant metastases following radiotherapy due to radioresistance.…”
Section: Introductionmentioning
confidence: 99%